Analysis of the influence of transformational leadership and readiness to change on the performance of female employees during the covid-19 pandemic - Dedy Se'u; Hermyn Hina; Yohana Setiawan (Institute of Computer Science (IOCS), 2023)
Many companies or organizations are just starting to stand so that quality Human Resources are needed. This study was conducted to determine the effect of transformational leadership and readiness to change on the performance of female employees during the Covid-19 pandemic at PT Ramayana Lestari Sentosa Tbk. Kupang City. The sample in this study were female employees of PT Ramayana Lestari Sentosa Tbk. Kupang City totaling 40 people. Data collection techniques using a questionnaire by giving respondents to choose alternative answers in the form of a check list with a two-pole verbal research scale. The results showed that the transformational leadership variable partially had a positive and significant effect on the performance of female employees during the COVID-19 pandemic, while the readiness to change variable had a significant negative effect on the performance of female employees during the Covid-19 pandemic. The readiness to change variable has a significant negative effect on the performance of female employees during the Covid-19 pandemic. The transformational leadership variable is 4.214 (sig.0.000) and the ttable value is 2.02809, then Ho is rejected and Ha is accepted, the readiness to change variable is -2.988 and the ttable value is 2.02809, then Ho is accepted and Ha is rejected.